Rancang Bangun Sistem Manajemen Informasi Aset Menggunakan Laravel (Studi Kasus: Universitas XYZ) - Naibaho, Steven; Maulani, Muhammad Ruslan; Hamidin, Dini (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2024)
The Universitas Logistik dan Bisnis Internasional’s current asset management system relies on written documentation, which presents several challenges. One such challenge is the difficulty in locating specific assets. One potential avenue for enhancing asset management is the development of an asset management information system. The system is designed to facilitate the management of campus assets, offering a range of features including the ability to record items and locations, generate reports in PDF format, and print item labels with integrated QR codes for enhanced searching capabilities. The system was developed using the Laravel framework with the Waterfall method, which includes the stages of needs analysis, system design, implementation, and testing. Each feature was designed to ensure more effective and efficient asset management in accordance with the specific requirements of the agency in question. The results demonstrate that this system is capable of increasing efficiency in the management of campus assets, facilitating asset tracking, and providing accurate and comprehensive reports. The implementation of this asset management information system is expected to make a significant contribution to asset management in the campus environment.